Intake, performance, meat quality and fatty acid profile of Nellore bulls finished in feedlot with diets containing dry corn gluten feed - Baldassini, Welder A. [UNESP]; Ferreira, Mateus S. [UNESP]; Santiago, Bismarck M. [UNESP]; Chardulo, Luis Artur L. [UNESP]; Curi, Rogério A. [UNESP]; Lanna, Dante P.D.; Ribeiro, Richard V. [UNESP]; Martins, Cyntia L. [UNESP]; Arrigoni, Mário [UNESP]; Machado Neto, Otávio Rodrigues [UNESP] (Elsevier, 2021)
We evaluate the effects of dry corn gluten feed (DCGF) levels in the finishing diet of Nellore cattle on feed intake, performance, carcass traits, meat quality and fatty acid profile. A hundred twenty non-castrated Nellore bulls (Bos indicus), with an average initial body weight of 361.66 ± 14.85 kg were used. Animals received feedlot diets containing different levels of DCGF (0, 18, 36 and 54%, dietary DM basis). This corn by-product, which is rich in fiber and protein, improves intake, performance, and hot carcass weight of animals, without impairing meat color and shear force (SF). Although backfat thickness was similar between the control and the DCGF treatments, there was a tendency towards a reduction in the intramuscular fat (IMF) content of Longissimus thoracis (LT) muscle, and a change of the IMF fatty acid profile of LT muscle at levels above 18% DCGF. Greater amounts of conjugated linoleic acid (CLA), saturated fatty acid (SFA), and monounsaturated fatty acids (MUFA) were found in animals finished with diets containing 18 and 36% DCGF when compared to the control diet, which may reflect the changes in rumen pH and biohydrogenation in response to changes in dietary carbohydrate source. Moreover, these results could be due the greater amounts of total SFA and MUFA found in DCGF compared to ground corn and soybean meal.
Keywords: Beef quality; Bos indicus; Carcass; Corn milling; Intramuscular fat